The Effect of the Project-Based Learning Model Based on Entrepreneurship Professional Learning Community (PJBL-EPLC) with a Deep Learning Approach on Enhancing Critical Thinking Skills and Entrepreneurial Attitudes - Elta Resmawati; Siti Darwa Suryani (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
The low level of students’ critical thinking skills and entrepreneurial attitudes in biology learning indicates the need for a contextual and meaningful learning model. This study aims to examine the effect of the Project-Based Learning model based on an Entrepreneurship Professional Learning Community (PjBL-EPLC) with a Deep Learning approach on students’ critical thinking skills and entrepreneurial attitudes at SMAN 2 Bengkulu City. This study employed a quasi-experimental method with a pretest-posttest nonequivalent control group design. The sample consisted of two classes, each with 36 students, selected using purposive sampling. The instruments included a critical thinking test and an entrepreneurial attitude questionnaire. Data were analyzed using inferential statistics based on prerequisite test results. The findings revealed significant differences in critical thinking skills (p = 0.006) and entrepreneurial attitudes (p = 0.001) between the experimental and control groups. These results indicate that the PjBL-EPLC model with a Deep Learning approach is more effective in improving students’ critical thinking skills and entrepreneurial attitudes compared to conventional learning.